Competitive and cooperative interactions between medial temporal and striatal learning systems. (January 2020) - Freedberg, Michael; Toader, Andrew C.; Wassermann, Eric M.; Voss, Joel L.
Abstract: The striatum and medial temporal lobes (MTL) exhibit dissociable roles during learning. Whereas the striatum and its network of thalamic relays and cortical nodes are necessary for nondeclarative learning, the MTL and associated network are required for declarative learning. Several studies have suggested that these networks are functionally competitive during learning. Since these discoveries, however, evidence has accumulated that they can operate in a cooperative fashion. In this review, we discuss evidence for both competition and cooperation between these systems during learning, with the aim of reconciling these seemingly contradictory findings. Examples of cooperation between the striatum and MTL have been provided, especially during consolidation and generalization of knowledge, and do not appear to be precluded by differences in functional specialization. However, whether these systems cooperate or compete does seem to depend on the phase of learning and cognitive or motor aspects of the task. The involvement of other regions, such as midbrain dopaminergic nuclei and the prefrontal cortex, may promote and mediate cooperation between the striatum and the MTL during learning. Building on this body of research, we propose a model for striatum-MTL interactions in learning and memory and attempt to predict, in general terms, when cooperation or competition will occur. Highlights: We reviewed literature on competition and cooperation between the striatal and medial temporal (MTL) learning networks. Cooperation appears to occur even when the networks are simultaneously engaged in different learning functions. Cooperation does appear to depend on the phase of learning and task demands. We present a model where striatal-MTL interactions are mediated by the prefrontal cortex and midbrain dopamine nuclei.